Pengaruh Jenis Tanaman Penolak Organisme Pengganggu Tanaman terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max (L.) Merr) yang Diusahakan Secara Organik - Kusheryani, Ina; Aziz, Sandra Arifin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
The purpose of this research is to determine the influence of repellent plant on growth and productivity of organic vegetable soybean. This research was conducted at Leuwikopo Research Station, from September 2004 to February 2005. Randomized Complete Block Design with one factor (type of repellent plant) and four replications was used. The type of repellent plant were Marigold (Tagetes erecta), Ocimum gratissimum, andropogon (Cymbopogon nardus), and leeks (Allium fistulosum).This research showed organic soybean with repellent plant had higher productivity than conventional soybean. Organic soybean with repellent plants had higher number of branches in 5 Weeks After Plant (WAP), the pod weight/plot, and 100 seeds dry weight. Growth and production of soybean were better under organic farming system than that under conventional farming. Soybean with repellent plant had lower total disease intensity than conventional treatment. Soybean with Tagetes erecta as repellent plant had lower total disease intensity than other repellent treatment. Key words: Organic vegetable soybean, repellent plant, pest and bulk disease intencity.